Professoras universitárias negras de língua inglesa do Brasil e o letramento racial crítico: práticas subversivas em narrativas autobiográficas. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Black people in Brazil commonly wear discrimination, racism and distance from places of success and prominence as their skin. When they are women, this dynamic is reinforced, since as stated by Sueli Carneiro (2011), the intersection of racial, gender and class oppressions submit black women to social asphyxia. For this reason, the image of black women is not recurrently associated with that of an English-speaker, or even who teaches that prestigious language. This research, located in applied linguistics with the narrative research methodology through autobiographical narratives, generated by semi-structured interviews, responds as five ESL professors from public institutions of higher education, from five different regions of Brazil, understand the interrelation between their identities, performances and the subversion they represent. What motivates the perspective adopted in the research is the importance of talking about and with black people without only emphasizing the suffering they experienced, in addition to denouncing it, talking about the success and hope of more results from anti-racist practices. The three research questions are: “how do black ESL professors, through their autobiographical narratives, relate their professional success to the racial issue?”; “How is critical racial literacy in the experiences of participating black university ESL professors?”; and “how do the participating professors perceive that their contribution to a more egalitarian society in relation to the intersection of gender and race has happened and is taking place?”. The theoretical framework that allows the analysis of autobiographical narratives is mainly based on perspectives such as black feminism with the researcher’s perspectives of Carneiro (2011 and 2018), Kilomba (2019) and hooks (2013, 2015 and 2019), intersectionality, based on Akotirene (2019) and Crenshaw (1998 and 2002) and Collins (2021), critical racial literacy, based on Ferreira (2014, 2015 and 2019) and the ESL teacher's identity, based on Kubota and Lin (2006). The results of the analysis indicate that although the teachers have faced racism on a daily basis since before entering and teaching in higher education, they understand that they are successful professionals and that they inspire other black women, as well as representing the demarcation of another corporeality than is understood to be the norm in ESL teaching and learning.
Keywords: Letramento racial crítico; professoras universitárias negras de língua inglesa; interseccionalidade; identidade docente de língua inglesa.; Critical racial literacy; black female ESL professors; intersectionality; ESL teacher’s identity.; CNPQ::LINGUISTICA, LETRAS E ARTES